2021
DOI: 10.3390/cancers13133265
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Derivatives Suppress Cancer Chemoresistance by Inhibiting Progesterone Receptor Membrane Component 1

Abstract: Progesterone receptor membrane component 1 (PGRMC1) is highly expressed in various cancer cells and contributes to tumor progression. We have previously shown that PGRMC1 forms a unique heme-stacking functional dimer to enhance EGF receptor (EGFR) activity required for cancer proliferation and chemoresistance, and the dimer dissociates by carbon monoxide to attenuate its biological actions. Here, we determined that glycyrrhizin (GL), which is conventionally used to ameliorate inflammation, specifically binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Firstly, knocking out PGRMC1 and/or PGRMC2 expression did not alter the ability of AG-205 to induce the formation of large endosomes in CHO-K1 and HeLa cells [16]. Secondly, and through a more direct approach, no binding activity of AG-205 to apo-or heme-dimerized PGRMC1 was observed by isothermal titration calorimetry analysis [17].…”
Section: Introductionmentioning
confidence: 94%
“…Firstly, knocking out PGRMC1 and/or PGRMC2 expression did not alter the ability of AG-205 to induce the formation of large endosomes in CHO-K1 and HeLa cells [16]. Secondly, and through a more direct approach, no binding activity of AG-205 to apo-or heme-dimerized PGRMC1 was observed by isothermal titration calorimetry analysis [17].…”
Section: Introductionmentioning
confidence: 94%
“…Since activated PGRMC1 may potentiate the oncogenic signaling of ERα and thereby promote breast cancer progression, it may serve as a therapeutic target. In this context, Kabe et al recently identified glycyrrhizin, a major component in licorice extract with anti-inflammatory and anti-viral effects [ 67 ], as a substance that directly binds PGRMC1 and inhibits some of its functions [ 68 ]. In a human colon cancer cell line, glycyrrhizin inhibited the interaction of PGRMC1 with EGFR, suppressing EGFR signaling and increasing chemosensitivity towards erlotinib and cisplatin [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Kabe et al recently identified glycyrrhizin, a major component in licorice extract with anti-inflammatory and anti-viral effects [ 67 ], as a substance that directly binds PGRMC1 and inhibits some of its functions [ 68 ]. In a human colon cancer cell line, glycyrrhizin inhibited the interaction of PGRMC1 with EGFR, suppressing EGFR signaling and increasing chemosensitivity towards erlotinib and cisplatin [ 68 ]. Future studies should investigate the effect of glycyrrhizin on PGRMC1 in the context of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, glycyrrhizin has been widely studied for combination chemotherapies involving cisplatin, 5-Fluorouracil, radiation, doxorubicin, paclitaxel, etc. [196][197][198][199][200][201][202][203][204][205][206].…”
Section: Bioactive Components Of Licoricementioning
confidence: 99%